What happens now? : reinvent yourself as a leader before your business outruns you - Hillen, John; Nevins, Mark D. (Findaway World : Tantor Audio, 2018)
Few leaders will admit it, but again and again the growth of their organizations outruns their skills. If you're one of those leaders, you know the result: as the job grows bigger than you are, you get disoriented by a world of unfamiliar challenges. You then hit a wall of ineffectiveness, a stall point. Why won't doubling down on the managerial and technical building blocks that have worked before help you out of a stall? Because you invariably neglect the new political, personal, strategic, and interpersonal skills needed to manage yourself and others. Predictable and inevitable, your stall then escalates into a crisis. And the crisis escalates faster the higher you go, since challenges of sophistication dwarf those of complexity at higher organizational levels. What Happens Now?: Reinvent Yourself as a Leader Before Your Business Outruns You helps you to embrace this reality. It shows how sophistication requires you do things you've never done before--inspire people, nurture relationships, energize teams, groom successors, influence stakeholders. What Happens Now? doesn't dwell on leadership theory and philosophy. As troubleshooters for leaders of all kinds, authors John Hillen and Mark Nevins focus on the most menacing issue they see in organizations every day: leaders who try to solve challenges solely by engineering solutions to more complexity-process mapping, data analytics, information systems, instant reports. The result? Organizational wreckage. Will this be your fate? Can you instead turn game-stopping stalls into personal growth and organization success? Can you struggle through the realization that you're the cause and launch the next phase of your lifelong leadership journey? Can you reinvent yourself? Hillen and Nevins show you how. If the dozens of leaders they profile can overcome these stalls, so can you. Foreword by Norman Augustine.